Astronomy in India : a historical perspective - Padmanabhan, Thanu (New Delhi, Springer, 2010)
ASTRONOMY IN INDIA A HISTORICAL PERSPECTIVE (HB 2014) PADMANABHAN T 9788184899979 1983 SPRINGERCBS Publishers & Distributors
Include bibliographical references.
Keywords: Astronomy- India; Astronomy